The geography of migratory movements in Europe from the Sixties to the present day - Christian Vandermotten; Gilles Van Hamme; Pablo Medina Lockhart (Belgeo)
Migratory movements, as well intra- as international, increased in Europe during the Nineties, after a slowing-down between the mid-Seventies and the end of the Eighties. The collapse of the Iron Curtain is only one reason among others explaining those growing migratory movements at the beginning of the Nineties. The geographical pattern of the migratory balances which emerged during the Nineties is much more complex than the Fordist one prevailing during the Sixties and the beginning of the Seventies. The migratory balances by age allows us to better understand the various new causes of the migratory patterns.